Participação administrativa processual na administração pública dialógica - Lima, Raimundo Marcio Ribeiro (2012)
The dissertation, which is based on the deductive method, by using general concepts of the theory of the administrative participation in the administrative process, addresses the importance of strengthening administrative and procedural activities of citizen involvement in public administration for the administrative consolidation of democracy in Brazil. The emergence of Administrative Law has particular importance for the understanding of its institutions and, of course, for the different fields of public administration. The authoritarian profile of this area of law still exists as a clear recollection of their origin, mainly based on a relationship of superiority of the state over the individuals. Indeed, does not even modern constitutionalism could print a true democracy administrative, since the constitutions were not properly observed by the Government. Furthermore, only the process of constitutionalization of administrative law legal relations took a more democratic profile. That is, the creation of an environment of dialogue with civil society is a recent achievement of the Brazilian government. As the administrative process involves dilemmas and solutions of state action, because it is revealed the expression government, the strengthening of institutions and principles related to the administrative procedure is important for role in making a more participatory relationship between state and citizen. Thus, administrative participation can be considered not only a mechanism of control and legitimacy of state action, but also for improvement and reduction of administrative costs, as a requirement of the principle of efficiency. The objective of this investigation is to assert as the administrative legal relation, the administrative legality, the administrative jurisdiction, the processuality administrative, the consensuality administrative and administrative justice, together with administrative participation, can contribute to a more democratic role of the Public Administration and, therefore, more dialogic and consolidator of the fundamental rights of citizens. Therefore, we highlight the importance of the administrative process and administrative participation as mechanisms for improving public policy and thus as a means of reducing administrative costs mediate the state